Active control of vibrations in pedestrian bridges - Álvaro Cunha (1999)
This paper, apart from making a brief general reference to vibration problems in pedestrian bridges, as well as to the form of modelling of dynamic pedestrian loads, presents the use of a predictive control strategy for the numerical simulation of the dynamic response of actively controlled structures of this type. The consideration of this control strategy permitted the development of a computational model, which was applied to the study of a pedestrian cable-stayed bridge, in order to show the interest and efficiency of the active control technique used.